Central America Education Strategy : An Agenda for Action - World Bank (Washington, DC, 2012)
The main objective of this regional paper is to provide an in-depth diagnostic of where Central American countries stand along several education dimensions, underscoring the most urgent and serious challenges and suggesting policy options to address them. The report focuses on El Salvador, Honduras, Guatemala, and Nicaragua because these countries have common geographic, political, and economic features which make them broadly comparable also from the standpoint of their education sectors. They face common challenges but they can also learn from each other. A comparison with other countries is also provided to be able to put in perspective the education performance and the development path and interventions applied in these four countries.